Mummies, tombs, and treasure : secrets of Ancient Egypt - Perl, Lila.; Weihs, Erika (New York : Clarion Books, 1987)
Text and photographs examine the mummies and tombs of ancient Egypt.
Includes index.
Bibliography: p. 113-114.
Keywords: Mummies -- Egypt -- Juvenile literature; Tombs -- Egypt -- Juvenile literature; Egypt -- Juvenile literature. -- Juvenile literature